PENGEMBANGAN KOMPETENSI GURU SMKN 1 LABANG BANGKALAN MELALUI PEMBUATAN MEDIA PEMBELAJARAN AUGMENTED REALITY DENGAN METAVERSE - Ariesta Kartika Sari; Puji Rahayu Ningsih; Wanda Ramansyah; Arik Kurniawati; Indah Agustien Siradjuddin; Mochammad Kautsar Sophan (LP2M Universitas Hasanuddin, 2020)
An Improvement on Competence of SMKN 1 Labang Bangkalan Educators by Creating Augmented Reality Learning Media Using MetaverseAbstract. Currently, technology has entered the Information Technology Era 4.0, where technology using the internet is increasingly being used. Along with the development of technology and information and referring to the competence of teachers in the Teacher Law and Lecturer Number 14 of 2005, a teacher is expected to be able to utilize technology, information and communication in the application of learning. This is needed in order to improve the quality of education and learning in schools. One of the efforts in increasing teacher competency related to instructional media is through training in making augmented reality learning media using the metaverse application. The learning media development activity is located at SMK Negeri 1 Labang Bangkalan Madura with the Participants being 14 teachers. The method of this activities is workshops and presentations. The evaluation method in this activity is through the distribution of the questionnaire response instruments. This activity produces: (a) augmented reality learning media by using the metaverse application and (b) teacher responses. This activity giving conclusion that: (a) training in the development of Augmented Reality learning media using metaverse application can develop the competency of teacher skills which related to learning media, (b) 100% of the activity participants expressed interest, and (c) 93% of the training participants stated that the development of media Augmented Reality learning by using the metaverse application is useful.Keywords: competence, learning media, Augmented Reality, MetaverseAbstrak. Saat ini teknologi telah memasuki Era Teknologi Informasi 4.0, yang mana teknologi dengan memanfaatkan internet makin banyak digunakan. Seiring dengan perkembangan teknologi dan informasi tesebut serta mengacu pada kompetensi guru dalam Undang-undang Guru dan Dosen Nomor 14 Tahun 2005 tersebut, maka seorang guru diharapkan mampu memanfaatkan teknologi, informasi dan komunikasi dalam penerapan pembelajaran. Hal ini diperlukan dalam rangka peningkatan kualitas pendidikan dan pembelajaran dalam sekolah. Salah satu upaya dalam peningkatan kompetensi guru terkait media pembelajaran adalah melalui adanya pelatihan pembuatan media pembelajaran Augmented Reality dengan menggunakan aplikasi metaverse. Kegiatan pengabdian pengembangan media pembelajaran ini bertempat di SMKN 1 Labang Bangkalan Madura, Peserta Kegiatan adalah guru-guru sebanyak 14 orang. Metode kegiatan pengabdian adalah berupa workshop dan presentasi. Metode evaluasi pada kegiatan pengabdian ini adalah melalui penyebaran instrumen angket respon. Kegiatan ini menghasilkan media pembelajaran Augmented Reality dengan menggunakan aplikasi metaverse serta respon guru. Kegiatan pengabdian ini menghasilkan kesimpulan bahwa: (a) pelatihan pengembangan media pembelajaran Augmented Reality dengan aplikasi metaverse dapat mengembangkan kompetensi keterampilan guru terkait media pembelajaran, (b) 100% peserta kegiatan menyatakan tertarik, dan (c) 93% peserta pelatihan menyatakan bahwa pengembangan media pembelajaran Augmented Reality dengan menggunakan aplikasi metaverse adalah bermanfaat.Kata Kunci: kompetensi, media pembelajaran, Augmented Reality, Metaverse